Far-reaching advances in the role of carbon nanotubes in cancer therapy - Dizaji, Babak Faraji; Khoshbakht, Saba; Farboudi, Amirnezam; Hasani Azarbaijan, Mohammadreza; Irani, Mohammad (Pergamon-Elsevier Science Ltd, 2020)
Cancer includes a group of diseases involving unregulated cell growth with the potential to invade or expand to other parts of the body, resulting in an estimate of 9.6 million deaths worldwide in 2018. Manifold studies have been conducted to design more efficacious techniques for cancer therapy due to the inadequacy of conventional treatments including chemotherapy, surgery, and radiation therapy. With the advances in the biomedical applications of nanotechnology-based systems, nanomaterials have gained increasing attention as promising vehicles for targeted cancer therapy and optimizing treatment outcomes. Owing to their outstanding thermal, electrical, optical and chemical properties, carbon nanotubes (CNTs) have been profoundly studied to explore the various perspectives of their application in cancer treatment. The current study aims to review the role of CNTs whether as a carrier or mediator in cancer treatment for enhancing the efficacy as well as the specificity of therapy and reducing adverse side effects. This comprehensive review indicates that CNTs have the capability to be the next generation nanomaterials to actualize noninvasive targeted eradication of tumors. However, further studies are needed to evaluate the consequences of their biomedical application before the transition into clinical trials, since possible adverse effects of CNTs on biological systems have not been clearly understood.
Keywords: Carbon nanotubes; Cancer treatment; Targeted drug delivery; Combination cancer therapy; Tumor ablation; Cancer cell lines